2020
DOI: 10.1177/0734242x20935174
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost biodiesel production using waste oil and catalyst

Abstract: With the production of renewable biofuels, concerns about the end of fossil fuels have been partially eliminated. On the other hand, the utilization of low-cost and waste materials to provide the raw essential substances to manufacture these fuels is of paramount importance. Biodiesel is one of these fuels and the required raw materials for the reaction are oil (triglycerides), alcohol and catalyst. In this work, travertine stone powder (as waste in the manufacture of building materials) was used as a catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Environmental issues linked with the production of the first generation of biofuels in cases where poor countries need to produce the waste amounts of biomass for the needs of OECD countries, the issues of deforestation, genetically modified crops, species loss, water usage and runoff, herbicide and pesticide use, soil degradation, and land energetic are being mitigated with the second generation of biofuel production. The second generation of biofuel involves the production of ethanol by the biochemical breakdown of lignocellulose, as well as the production of biodiesel from a range of biomass processes, such as fast pyrolysis for biooil or gasification and the Fischer-Tropsch process for synthetic biodiesel [29,31,74].…”
Section: Different Models For Biorefineries and Centralizationmentioning
confidence: 99%
“…Environmental issues linked with the production of the first generation of biofuels in cases where poor countries need to produce the waste amounts of biomass for the needs of OECD countries, the issues of deforestation, genetically modified crops, species loss, water usage and runoff, herbicide and pesticide use, soil degradation, and land energetic are being mitigated with the second generation of biofuel production. The second generation of biofuel involves the production of ethanol by the biochemical breakdown of lignocellulose, as well as the production of biodiesel from a range of biomass processes, such as fast pyrolysis for biooil or gasification and the Fischer-Tropsch process for synthetic biodiesel [29,31,74].…”
Section: Different Models For Biorefineries and Centralizationmentioning
confidence: 99%
“…Moreover, logistics and collection infrastructure are not well developed and hence could be a hurdle due to scattered sources ( Sajjadi et al, 2016 ). Extensive literature has been published on the utilization of waste oil as biodiesel feedstock ( Yaakob et al, 2013 ; Hajjaria et al, 2017 ; Fonseca et al, 2019 ; Talavari et al, 2020 ).…”
Section: Conventional Feedstocks Used For Biodiesel Productionmentioning
confidence: 99%
“…Similarly, lipase obtained from staphylococcal strains has been used in the manufacture of antioxidants such as ethanol-acetate and eugenyl benzoate (Horchani et al, 2012). Dai and Xia, 2005;Herrera-Lopez, 2012;Horchani et al, 2012;Bancerz, 2017;Kumar et al, 2017;Memarpoor-Yazdi et al, 2018 Pulp and paper Hydrolysis Paper with improved quality Demuner et al, 2011;Horchani et al, 2012;Liu et al, 2012;Almeida et al, 2018;Patel et al, 2019 Washing Hydrolysis Removal of fats Niyonzima and More, 2015;Phuah et al, 2015;Kumar et al, 2016;Unni et al, 2016;Holland and Sajic, 2017;Mehta et al, 2017;Saraswat et al, 2017;Abol-Fotouh et al, 2021 Biodiesel Transesterification, hydrolysis, synthesis Biodiesel production Karmee et al, 2015;Tran et al, 2016;Khosla et al, 2017;Tian et al, 2017;Li et al, 2020;Sorte et al, 2020;Talavari et al, 2020 Leather Hydrolysis Leather products Kavitha et al, 2018;Rashid et al, 2018 Cosmetics Synthesis Emulsifiers, moisturizers Gupta et al, 2015;Kim et al, 2015;Ugo et al, 2017;Uppada et al, 2017;Tufiño et al, 2019 Environmental protection Transesterification, hydrolysis Environmental detection and repair Lauprasert et al, 2017;Bucur et al, 2018;Hassan et al, 2018;…”
Section: Medical Applications Of Microbial Lipasesmentioning
confidence: 99%
“…Biodiesel is comprised of a fatty-acid monoester that is generated by transesterification of triglycerides from fats (Filho et al, 2019). At present, biodiesel is produced mainly by alkaline catalysis and supercritical fluid catalysis (Mandolesi De Araújo et al, 2013); lipase catalysis has been used in the industrial production of biodiesel (Li et al, 2020;Puna et al, 2020;Talavari et al, 2020). According to the research of Tran et al (2016) the biodiesel conversion rate using sunflower oil in a packed bed reactor with immobilized Burkholderia lipase, they found that a single packed bed reactor resulted in a 67% biodiesel conversion rate.…”
Section: Applications Of Microbial Lipases In Biodiesel Productionmentioning
confidence: 99%